Pengaruh Debt To Asset Ratio (DAR), Working Capital Turnover (WCT), dan Price Earning Ratio (PER) Terhadap Harga Saham : Studi Kasus: Perusahaan Farmasi Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2023 - Risyda Nurfadilah; Fathihani Fathihani (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This research aims to analyze the influence of Debt to Asset Ratio (DAR), Working Capital Turnover (WCT), and Price Earning Ratio (PER) on the share prices of pharmaceutical companies listed on the Indonesia Stock Exchange (BEI) in the 2019-2023 period. The method used in this research is multiple linear regression analysis, with data taken from the annual financial reports of pharmaceutical companies listed on the IDX. The approach in this research uses a quantitative approach, and based on its objectives, this type of research is causal. The independent variables in this research include Debt to Asset Ratio (DAR), Working Capital Turnover (WCT), and Price Earning Ratio (PER) and the dependent variable in this research is Stock Price. The population of this research is Pharmaceutical Companies listed on the Indonesia Stock Exchange (BEI), totaling 17 Pharmaceutical Companies for the 2019-2023 period. This research uses the Purposive Sampling method, so the number of samples in this research is 50 samples. This research uses documentation techniques and SPSS 26 application tools. The results of this research show that the Debt to Asset Ratio (DAR), Working Capital Turnover (WCT), and Price Earning Ratio (PER) influence the share prices of pharmaceutical companies listed on the Indonesia Stock Exchange (BEI) in the 2019-2023 period.